2016
DOI: 10.5539/ijel.v6n6p221
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Emotional Intelligence and Reading Comprehension of Iranian EFL Impulsive vs. Reflective Students

Abstract: The present article aimed at investigating the relationship between the emotional intelligence and reading comprehension of Iranian EFL impulsive and reflective students. To do so, 121 students based on a PET test were selected. Then, they answered a translated version of emotional intelligence and did a reading comprehension test. Later, they filled out impulsiveness questionnaire reflectiveness questionnaire. The results of these questionnaires and the reading test were compared. The first finding of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Finally, sociality came with the least correlation among the other components (0.876). This finding is consistent with the previous result mentioned by many researchers such as Dehkordi and Shirani Bidabadi (2015); Tabrizi and Esmaeili (2016) and Mohammadi et al (2020). In their studies, they reported that there was a significantly positive relationship between EFL students' emotional intelligence and their reading comprehension.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, sociality came with the least correlation among the other components (0.876). This finding is consistent with the previous result mentioned by many researchers such as Dehkordi and Shirani Bidabadi (2015); Tabrizi and Esmaeili (2016) and Mohammadi et al (2020). In their studies, they reported that there was a significantly positive relationship between EFL students' emotional intelligence and their reading comprehension.…”
Section: Discussionsupporting
confidence: 91%
“…Mohammadi et al (2020) confirm that, among the elements of self-regulated learning, cognitive and metacognitive strategies are controlling predictors of reading comprehension and problem-solving. Tabrizi and Esmaeili (2016) examined the correlation between emotional intelligence and reading comprehension between impulsive and reflective Iranian EFL learners. They concluded that the relationship between these two variables was positive.…”
Section: Emotional Intelligencementioning
confidence: 99%
“…Ateş 2019found a positive correlation between EI and Turkish EFL learners' reading comprehension skill as well as a negative correlation between EI and the learners' reading anxiety. Nemat Tabrizi and Esmaeili (2016) investigated the relationship between emotional intelligence and reading comprehension for impulsive and reflective Iranian EFL learners. They found a significant relationship between Iranian EFL learners' emotional intelligence and their reading comprehension.…”
Section: Related Studies On Ei Metacognitive Strategies and L2 Learningmentioning
confidence: 99%
“…However, existing research has primarily focused on singular reading methods, often failing to compare the influence of different methods simultaneously, or to consider how individual characteristics, such as cognitive styles, may interact with these methods. While there are studies that acknowledge the impact of cognitive styles like impulsivity (i.e., quick decision-making and risk-taking) and reflectivity (i.e., deliberate and thorough problem-solving) on general reading comprehension (e.g., Amiry & Mall-Amiri, 2015; Nemat Tabrizi & Esmaeili, 2016;Nisa et al, 2018), the impact of these cognitive styles on specific reading methods remains underexplored.…”
Section: Introductionmentioning
confidence: 99%